2012
DOI: 10.1093/schbul/sbr196
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Psychotic Symptoms Are Prevalent in Disorders of Anxiety and Depression, Impacting on Illness Onset, Risk, and Severity--Implications for Diagnosis and Ultra-High Risk Research

Abstract: Copresence of psychotic symptomatology in disorders of anxiety and depression is common and a functionally and etiologically highly relevant feature, reinforcing the view that psychopathology is represented by a network or overlapping and reciprocally impacting dimensional liabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
320
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 343 publications
(352 citation statements)
references
References 50 publications
28
320
2
2
Order By: Relevance
“…Our finding that subclinical psychotic experiences have a negative impact on the clinical manifestation of depression, both in terms of severity and of development over time, concurs with earlier work in the general population (Olfson et al 2002;van Rossum et al 2011;Wigman et al 2012) as well as in a clinical sample (Perlis et al 2011). In the latter, it was shown that depressed individuals with psychotic experiences responded less well to four consecutive pharmacological interventions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that subclinical psychotic experiences have a negative impact on the clinical manifestation of depression, both in terms of severity and of development over time, concurs with earlier work in the general population (Olfson et al 2002;van Rossum et al 2011;Wigman et al 2012) as well as in a clinical sample (Perlis et al 2011). In the latter, it was shown that depressed individuals with psychotic experiences responded less well to four consecutive pharmacological interventions.…”
Section: Discussionsupporting
confidence: 91%
“…Symptoms of psychosis (Hanssen et al 2003;Varghese et al 2011;Kelleher et al 2012b;Wigman et al 2012) and bipolar disorder (Angst et al 2010;Nusslock & Frank, 2011), at clinical and subclincal levels of expression, commonly occur in the context of major depressive disorder (MDD). This reflects overlap between affective and psychotic disorders in genetic ) and environmental risk factors (Weiser et al 2005), as well as in underlying endophenotypes, for example (neuro)cognitive, social and emotional dysfunctions (Weiser et al 2005;Hill et al 2009;Simonsen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, more research on underlying mechanisms is 13 required. The results of the present study show that PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology, in line with previous research (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014). Therefore, assessment of PE in individuals with non-psychotic psychopathology should be incorporated both in clinical practice and in future research, as previously suggested (Kelleher et al, 2013), in order to identify individuals at risk of suicidal behaviour.…”
Section: Discussionsupporting
confidence: 89%
“…PE were identified as a risk factor for several mental health outcomes including both psychotic (Kaymaz et al, 2012;Linscott and van Os, 2013) and non-psychotic psychopathology (Kelleher et al, 2012b) and are associated with increased treatment use and need for care in general population samples (Murphy et al, 2012). Moreover, PE serve as an indicator of illness severity and poor outcome in persons with non-psychotic psychopathology (Guloksuz et al, 2015;Kelleher et al, 2012b;Perlis et al, 2011;Wigman et al, 2012;Wigman et al, 2014) A recent meta-analysis reported that general population individuals with PE had an increased risk of both suicidal thoughts (i.e. suicidal ideation or suicidal plans) and suicidal behaviour (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Much research has established that psychotic experiences have a higher prevalence in the general population than psychotic disorders [1][2][3][4]. A meta-analysis of all community studies of psychotic experiences in children and adolescents found a median population prevalence of 17% in children aged 9-12 years and 7.5% in those aged 13-18 years [5].…”
Section: Introductionmentioning
confidence: 99%